2018
DOI: 10.1145/3274396
|View full text |Cite
|
Sign up to set email alerts
|

Personal Informatics in Interpersonal Contexts

Abstract: Personal informatics systems for supporting health largely grew out of a "self"-centric orientation: self-tracking, self-reflection, self-knowledge, self-experimentation, self-improvement. Health management, however, even when self-driven, is inherently social and depends on a person's direct relationships and broader sociocultural contexts, as an emerging line of research is coming to recognize, study, and support. This is particularly true in the case of mental health. In this paper, we engage with individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(13 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…A few HCI researchers have adopted similar ecological approaches that rely on Bronfenbrenner's ecological theory of development for children [11] as a lens to understand the role of diferent social actors in promoting healthy eating habits [38], information brokerage [68], and providing emotional support [87]. In the context of supporting self-management, previous research in HCI used the lens of Bronfenbrenner's social systems [11] to understand the role of social contacts when managing their depression with technology [14,59].…”
Section: Socialmentioning
confidence: 99%
“…A few HCI researchers have adopted similar ecological approaches that rely on Bronfenbrenner's ecological theory of development for children [11] as a lens to understand the role of diferent social actors in promoting healthy eating habits [38], information brokerage [68], and providing emotional support [87]. In the context of supporting self-management, previous research in HCI used the lens of Bronfenbrenner's social systems [11] to understand the role of social contacts when managing their depression with technology [14,59].…”
Section: Socialmentioning
confidence: 99%
“…In order to better characterize a quantified self experience, researchers propose conceptual models [ 5 , 24 , 25 ]. Here, we review three models of personal informatics for behavior change, presented in chronological order.…”
Section: Characterization Of the Quantified Self Movementmentioning
confidence: 99%
“…In order to better characterize the quantified self experience users go through, some researchers have attempted to derive conceptual models. In 2019, Vizer et al have identified four main models related to the tracking process but we will ignore two of them as they focus on users who are already patients, hereby involving a specific clinical context which is out of scope for our study [3,22,23].…”
Section: Conceptual Modelsmentioning
confidence: 99%